Wings of fire. Book four, The dark secret : the graphic novel - Sutherland, Tui, 1978-; Deutsch, Barry; Swirsky, Rachel (Graphix, 2021)
The young dragon Starflight is stolen by a group of dragons who turn out to be of his own tribe of NightWing, and takes it as an opportunity to learn about his own magical powers, who the tribe is allied with in the war, and where the NightWings have been hiding and living all this time. The truth is horrible--the NightWings live in a dark place of misery, and have taken captive innocent RainWings as well. Starflight must escape back to his friends--the fate of two kingdoms rests with him now.